Assessing the Amount of Data per Second to Measure Tactical Variables in Team Sports - Markel Rico-González; Asier Los Arcos; Daniel Rojas-Valverde; Carlos D. Gómez-Carmona; José Pino-Ortega (Journal of Coaching and Sports Science, 2023)
Sampling frequency of microsensors that measure the position of the players in team sports is a variable that could affect the accuracy of the measurement. The aim of the present study was to assess the impact of the sampling frequency on the measurement of a collective tactical behaviour variable: the total area (TA). Sixteen young U16 male soccer players participated in the study. They carried out three controlled tasks. Tactical variable was measured by a radio ultra-wide band technology (IMU; WIMU PROTM, RealTrack Systems, Almeria, Spain). For TA different sampling frequencies were applied (i.e. 1 Hz, 2 Hz, 4 Hz and 10 Hz). Trivial differences (p more than 0.05) were found between the TA values across the different amounts of inserted data per second across Task 1 (ES= 0.04-0.08), Task 2 (ES= 0.01-0.09) and Task 3 (ES= -0.03-0.04). Also High to perfect ICCs (0.91-1) and linear correlations (r= 0.961-1; p less than 0.01) were found among the TA values obtained through all sampling frequencies. The sampling frequency (i.e. 1 Hz, 2 Hz, 4 Hz and 10 Hz) does not affect the measurement of total area during tactical behaviour analysis but does significantly affect the change in centroid position measurement. Thus, it is recommended the use of 1 Hz to measure TA, but further studies should analyse the impact of lower than 1 Hz and greater than 10 Hz sampling frequencies to measure this collective tactical behavior.